Investigating the Effects of Climate Change on Structural Actions - Orcesi, André; O'Connor, Alan; Diamantidis, Dimitris; Sykora, Miroslav; Wu, Teng; Akiyama, Mitsuyoshi; Alhamid, Abdul Kadir; Schmidt, Franziska; Pregnolato, Maria; Li, Yue; Salarieh, Babak; Salman, Abdullahi M.; et al. (Structural engineering international : journal of the International Association for Bridge and Structural Engineering (IABSE), 2022)
The changing climate with resulting more extreme weather events will likely impact infrastructure assets and services. This phenomenon can present direct threats to the assets as well as significant indirect effects for those relying on the services those assets deliver. Such threats are path-dependent and place-specific, as they strongly depend on current and future climate variability, location, asset design life, function and condition. One key question is how climate change is likely to increase both the probability and magnitude of extreme weather events under different scenarios of climate change. To address this issue, this paper investigates selected effects of climate change and their consequences on structural performance, in the context of evolving loading scenarios in three different continental regions: Europe, North America, and Asia. The aim is to investigate some main place-specific changes of the exposure in terms of intensity/frequency of extreme events as well as the associated challenges, considering some recent activities of members of the IABSE TG6.1. Climate change can significantly affect built infrastructure and the society by increasing the occurrence and magnitude of extreme events and increasing potential losses. Therefore, specific relationships relating hazard levels and structural vulnerability to climate change effects should be determined.